Usefulness of Sonography in Evaluating Children Suspected of Malrotation: Comparison With an Upper Gastrointestinal Contrast Study. (11th September 2015) - Zhou, Lu-yao; Li, Shu-rong; Wang, Wei; Shan, Quan-yuan; Pan, Fu-shun; Liu, Jun-cheng; Xie, Xiao-yan
Abstract : Objectives: The purpose of this study was to prospectively evaluate the value of sonography in working up or ruling out malrotation by 3 sonographic features (inversion of the superior mesenteric artery and superior mesenteric vein, the whirlpool sign, and an intraperitoneal transverse duodenum) and comparing it with an upper gastrointestinal (GI) contrast study. Methods: A total of 70 pediatric patients who underwent detailed abdominal sonography to rule out intestinal malrotation were included. Twenty‐three of them also underwent an upper GI contrast study. Surgery or clinical follow‐up was taken as the reference standard. Statistical analysis was performed with the χ 2 test. Results: Twenty‐three patients had a diagnosis of malrotation by surgical findings. With the combination of all 3 sonographic features, the sensitivity, specificity, and accuracy of sonography for determining malrotation were 100% (23 of 23), 97.8% (46 of 47), and 98.6% (69 of 70), respectively, whereas the sensitivity, specificity, and accuracy of the upper GI study were 40% (4 of 10), 64.3% (9 of 14), and 56.5% (13 of 23; P < .001). Combined anomalies in 2 patients and complications in 2 patients were also detected by sonography. Conclusions: By combining inversion of the superior mesenteric artery and superior mesenteric vein, the whirlpool sign, and an intraperitoneal transverse duodenum, sonography might be more valuable for accurately working up or ruling out pediatric malrotation than an upper GI contrast study. In addition, sonography could provide extra information, such as combined anomalies and intestinal necrosis, to help management.